A Methyltransferase Trio Essential for Phosphatidylcholine Biosynthesis and Growth. Issue 2 (5th December 2018) - Liu, Yu-chi; Lin, Ying-Chen; Kanehara, Kazue; Nakamura, Yuki
Abstract : Three phospho-base N-methyltransferases have tissue-specific functions in phosphatidylcholine biosynthesis, which is essential for plant growth. Abstract: Phosphatidylcholine (PC) is a primary class of membrane lipids in most eukaryotes. In plants, the primary PC biosynthetic pathway and its role in plant growth and development remain elusive due to lack of a mutant model with substantially decreased PC content. Recently, a double mutant of Arabidopsis ( Arabidopsis thaliana ) PHOSPHO-BASE N -METHYLTRANSFERASE 1 (PMT1) and PMT3 was reported with reduced PC content and defective plant growth. However, residual PC content as well as the nonlethal phenotype of the mutant suggests an additional enzyme contributes to PC biosynthesis. In this article, we report on the role of three PMTs in PC biosynthesis and plant development, with a focus on PMT2. PMT2 had the highest expression level among the three PMTs, and it was highly expressed in roots. The pmt1 pmt2 double mutant enhanced the defects in root growth, cell viability, and PC content of pmt1, suggesting that PMT2 functions together with PMT1 in roots. Chemical inhibition of PMT activity in wild-type roots reproduced the short root phenotype observed in pmt1 pmt2, suggesting that PMT1 and PMT2 are the major PMT isoforms in roots. In shoots, pmt1 pmt2 pmt3 enhanced the phenotype of pmt1 pmt3, showing seedling lethality and further reduced PC content without detectable de novo PC biosynthesis. These results suggest that PMTs catalyze an essential reaction step in PC biosynthesis and that the three PMTs have differential tissue-specific functions in PC biosynthesis and plant growth.